The fcc solid solution stability in the Co-Cr-Fe-Mn-Ni multi-component system. (15th April 2017) - Bracq, Guillaume; Laurent-Brocq, Mathilde; Perrière, Loïc; Pirès, Rémy; Joubert, Jean-Marc; Guillot, Ivan
Abstract: The phase stability of the fcc solid solution in the Co-Cr-Fe-Mn-Ni system was theoretically and experimentally investigated. Using the Calphad approach and a new database (TCHEA1) devoted to high entropy alloys (HEA), the stable phases of 10 626 compositions could be calculated, depending on the temperature. 11 alloys were also processed and characterized. The comparison between calculations and experimental results indicates that the fcc solid solution is accurately described by the TCHEA1 database but, the σ phase is more stable than the calculation predictions. It was shown that the fcc phase is stable over a wide range of compositions, which was completely described. Now it is possible to choose a priori a composition which will form a solid solution within the Co-Cr-Fe-Mn-Ni system. Finally, it was proven that Cr and Mn destabilize the fcc solid solution, unlike Ni and Co. Graphical abstract: Image 1